Identifying disability level in multiple sclerosis patients in a U.S.-based health plan claims database. (1st January 2021) - Berkovich, Regina; Fox, Edward; Okai, Annette; Ding, Yao; Gorritz, Magdaliz; Bartolome, Lauren; Wade, Rolin L.; Su, Wendy; Johnson, Kristen M.; Russo, Patricia
Abstract: Aims: In clinical trials, disability progression in multiple sclerosis (MS) is measured by the Kurtzke expanded disability status scale (EDSS), which is not captured in routine clinical care in the U.S. This study developed a claims-based disability score (CDS) based on the EDSS for assigning MS disability level in a U.S. claims database. Methods: This retrospective cohort study of patients with MS in the U.S., utilized adjudicated health plan claims data linked to electronic medical records (EMRs) data. Patients were identified between 1 January 2012 and 31 December 2016 and indexed on the first date of MS diagnosis. The CDS was developed to assign disability level at baseline using claims and ambulatory EMR records observed over the 1-year baseline period. All-cause healthcare costs were assessed by baseline disability level to validate the CDS. Results: In total, 45, 687 patients were identified in claims (full sample) and 1, 599 linked to EMR (core sample). Over half of patients in both samples were classified with mild disability at baseline. Adjusted healthcare costs in patients with moderate and severe disability were 15% ( p <.0001) and 20% higher, respectively, than in patients with mild disability at baseline in the full sample. Disease-modifying therapy (DMT) costs accounted for 89%, 82%, and 78% of outpatient pharmacy costs in patients with mild, moderate, and severe disability, respectively. Conclusions: The CDS is the first claims-based measure of MS disability utilizing data from EMR. This novel measure advances the opportunity to examine outcomes by disability accumulation in the absence of standard markers of disease progression. Although formal validation of the CDS was not possible due to lack of available EDSS in the EMR, the economic burden results align with prior publications and show that healthcare costs increase with increasing disability. Future validation studies of the CDS are warranted.